Trade-off between interface stiffening and Young's modulus weakening in graphene/PMMA nanocomposites. (7th July 2022) - Cui, Yuanyuan; Wang, Guorui; Wang, Wenxiang; Cui, Xuwei; Dong, Wenlong; Wang, Congying; Jin, Meihua; He, Tao; Zhang, Zhong; Liu, Luqi
Abstract: Mechanical performance of graphene-based polymer nanocomposites is reported to be far below theoretical predictions. A critical factor lies in the weak bonding of graphene/polymer interfaces. Chemical functionalization is deemed as a common strategy to improve the interfacial adhesion between graphene and polymer, however, the creation of structural defects in graphene lattice is inevitable during such a chemical process. It hence calls for a balance in the design of graphene-based nanocomposites between the interface strengthening and mechanical degradation of graphene itself. Herein, mechanically exfoliated monolayer graphene is oxidized and atomic force microscopy (AFM) is performed to quantify the dependence of Young's modulus of graphene on the functionalization degree. In situ tensile-micro Raman spectroscopy is utilized to measure the interfacial properties between functionalized graphene and poly (methyl methacrylate) (PMMA) at the microscopic level. An optimal functionalization degree is determined to maximize the reinforcing effect of nanocomposites. Our results will be helpful to design various nanofiller-based composites with high mechanical performance. Graphical abstract: Image 1